Nauczanie języka kaszubskiego. Wokół ideologii jezyków kolateralnych - Dołowy-Rybińska, Nicole (Slavia Occidentalis, 2022)
The article discusses the educational consequences of the collateral nature of the Kashubian language in relation to Polish. The collateral nature is defined as the languages’ mutual intelligibility resulting from their formal proximity and the lack of political independence of the language community. Based on longterm field research and in-depth interviews, the analysis touches upon language ideologies in Kashubia which directly impact the process of teaching the Kashubian language. These ideologies – the assumptions about the language and its users rooted in social consciousness – refer to the status of the Kashubian language, its dialectal nature, and the legitimate speakers of Kashubian. Language ideologies related to the collateral nature of Kashubian are responsible for the choice of the teaching methods, the distrust of people associated with education (parents, teachers, students) as to the meaningfulness of teaching, as well as the relationship between the language learnt and spoken by the community